Perlindungan Hukum atas Waktu Kerja dan Waktu Istirahat bagi Buruh di Kota Bandar Lampung - Syofia Gayatri; Ahmad Khudlori; Ardi Satriadi; Muchlis Sadzili (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Legal protection of working hours and rest periods is part of the normative rights of workers, guaranteed by the 1945 Constitution of the Republic of Indonesia and labor laws and regulations. This study aims to analyze the implementation of legal protection of working hours and rest periods for workers in Bandar Lampung City, as well as to identify the factors hindering it following the enactment of Government Regulation Number 35 of 2021. This research uses a qualitative approach, employing a normative juridical legal research method with a statutory approach, supported by empirical data obtained through interviews with labor unions and the Bandar Lampung City Manpower Office. The results show that legal protection of working hours and rest periods has not been fully implemented optimally. Violations were still found regarding overtime hours, fulfillment of rest periods, and the provision of food and drinks for workers during overtime. The main obstacles include weak supervision, limited dissemination of regulations, an imbalance in bargaining positions between workers and employers, and the economic conditions of workers. Strengthening supervision and fostering synergy among stakeholders are necessary to ensure effective legal protection.